Ontogenic stage-associated SA response contributes to leaf age-dependent resistance in Arabidopsis and cotton - Hu, Lanxi; Mijatovic, Jovana; Kong, Feng; Kvitko, Brian; Yang, Li (Frontiers in Plant Science, 2024)
As leaves grow, they transition from a low-microbe environment embedded in shoot apex to a more complex one exposed to phyllosphere microbiomes. Such change requires a coordinated reprogramming of cellular responses to biotic stresses. It remains unclear how plants shift from fast growth to robust resistance during organ development. Here, we reported that salicylic acid (SA) accumulation and response were temporarily increased during leaf maturation in herbaceous annual Arabidopsis. Leaf primordia undergoing active cell division were insensitive to the elicitor-induced SA response. This age-dependent increase in SA response was not due to prolonged exposure to environmental microbes. Autoimmune mutants with elevated SA levels did not alter the temporal pattern dependent on ontogenic stage. Young Arabidopsis leaves were more susceptible than mature leaves to Pseudomonas syringae pv. tomato (Pto) DC3000 cor- infection. Finally, we showed a broadly similar pattern in cotton, a woody perennial, where young leaves with reduced SA-signaling were preferentially invaded by a Xanthomonas pathogen after leaf surface infection.